Prevalence factors associated with vision impairment and blindness among individuals 85 years and older in Russia - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Rakhimova, Ellina M.; Rusakova, Iuliia A.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Gilmanshin, Timur R.; Zainullin, Rinat M.; Bolshakova, Natalia I.; Safiullina, Kamilia R.; Gizzatov, Ainur V.; et al. (JAMA network open, 2021)
Visual performance is important for quality of life. However, vision impairment among adults 85 years and older has not been intensively examined.To assess the prevalence of mild vision impairment (VI), moderate to severe vision impairment, and blindness and the factors associated with these conditions among a population 85 years and older.The Ural Very Old Study was a population-based cohort study conducted in rural and urban areas in Bashkortostan, Russia from 2017 to 2020. Among 1882 eligible individuals 85 years and older, 1526 participants (81.1%) were enrolled.Ophthalmologic, physical, and mental examinations.Prevalence of vision impairment and blindness based on best-corrected visual acuity (BCVA; measured using modified Early Treatment of Diabetic Retinopathy Study charts) in the better eye or both eyes. Mild vision impairment was defined as BCVA worse than 6/12 to 6/18, and moderate to severe VI was defined as BCVA worse than 6/18 but equal to or better than 3/60. Blindness was defined as BCVA worse than 3/60.Among 1526 participants, 1149 individuals (75.3%; 846 women [73.6%]; mean [SD] age, 88.2 [2.8 years]) had available BCVA measurements and were included in the present analysis. Mild vision impairment was present in 114 individuals (9.9%; 95% CI, 8.2%-11.7%), moderate to severe VI in 562 individuals (48.9%; 95% CI, 46.0%-51.8%), and blindness in 68 individuals (5.9%; 95% CI, 4.6%-7.3%). Factors associated with moderate to severe VI were cataracts (324 individuals [57.7% of those with moderate to severe VI and 28.2% of total population; 95% CI, 25.6%-30.8%]), secondary cataracts (4 individuals [0.7% of those with moderate to severe VI and 0.3% of total population; 95% CI, 0%-0.7%]), age-related macular degeneration (78 individuals [13.9% of those with moderate to severe VI and 6.8% of total population; 95% CI, 5.3%-8.3%]), glaucoma (45 individuals [8.0% of those with moderate to severe VI and 3.9% of total population; 95% CI, 2.8%-5.0%]), corneal opacifications (26 individuals [4.6% of those with moderate to severe VI and 2.3% of total population; 95% CI, 1.4%-3.1%]), myopic maculopathy (13 individuals [2.3% of those with moderate to severe VI and 1.1% of total population; 95% CI, 0.5%-1.7%]), and nonglaucomatous optic nerve damage (4 individuals [0.7% of those with moderate to severe VI and 0.3% of total population; 95% CI, 0%-0.7%]). Factors associated with blindness were cataracts (33 individuals [48.5% of those with blindness and 2.9% of total population; 95% CI, 1.9%-3.8%]), age-related macular degeneration (15 individuals [22.1% of those with blindness and 1.3% of total population; 95% CI, 0.7%-2.0%]), glaucoma (7 individuals [10.3% of those with blindness and 0.6% of total population; 95% CI, 0.2%-1.1%]), myopic maculopathy (3 individuals [4.4% of those with blindness and 0.3% of total population; 95% CI, 0%-0.6%]), and corneal opacifications (2 individuals [2.9% of those with blindness and 0.2% of total population; 95% CI, 0%-0.4%]). Higher moderate to severe VI prevalence was associated with older age (odds ratio [OR], 1.19; 95% CI, 1.11-1.28; P < .001), higher blood pressure (OR, 1.01; 95% CI, 1.00-1.02; P = .03), lower hand grip force (OR, 0.88; 95% CI, 0.83-0.95; P < .001), lower score on the Mini-Mental State Examination (OR, 0.95; 95% CI, 0.92-0.98; P < .001), lower prothrombin index (OR, 0.93; 95% CI, 0.89-0.97; P < .001), lower refractive error (OR, 0.91; 95% CI, 0.85-0.97; P = .006), and lower prevalence of previous cataract surgery (OR, 0.48; 95% CI, 0.33-0.68; P < .001).In this cohort study of individuals 85 years and older, the prevalence of moderate to severe VI and blindness was relatively high. Cataracts were the main reversible condition associated with vision loss, and age-related macular degeneration, glaucoma, and myopic maculopathy were the main irreversible conditions. Because a higher prevalence of moderate to severe VI was associated with lower cognitive function and physical strength, improvement of vision through increases in cataract surgery and measures to prevent and treat irreversible conditions may help to improve cognitive function and physical strength.